Effect of ocean acidification on the growth, response and hydrocarbon degradation of coccolithophore-bacterial communities exposed to crude oil - Fahmi, Afiq Mohd (2023)
Hydrocarbon-degrading bacteria, which can be found living with eukaryotic phytoplankton, play a pivotal role in the fate of oil spillage to the marine environment. Considering the susceptibility of calcium carbonate-bearing phytoplankton under future ocean acidification conditions and their oil-degrading communities to oil exposure under such conditions, we investigated the response of non-axenic E. huxleyi to crude oil under ambient versus elevated CO2 concentrations. Under elevated CO2 conditions, exposure to crude oil resulted in the immediate decline of E. huxleyi, with concomitant shifts in the relative abundance of Alphaproteobacteria and Gammaproteobacteria. Survival of E. huxleyi under ambient conditions following oil enrichment was likely facilitated by enrichment of oil-degraders Methylobacterium and Sphingomonas, while the increase in relative abundance of Marinobacter and unclassified Gammaproteobacteria may have increased competitive pressure with E. huxleyi for micronutrient acquisition. Biodegradation of the oil was not affected by elevated CO2 despite a shift in relative abundance of known and putative hydrocarbon degraders. While ocean acidification does not appear to affect microbial degradation of crude oil, elevated mortality responses of E. huxleyi and shifts in the bacterial community illustrates the complexity of microalgal-bacterial interactions and highlights the need to factor these into future ecosystem recovery projections.